Tenure profiles and efficient separation in a stochastic productivity model - I. Sebastian Buhai; Coen N. Teulings (Institute for the Study of Labor (IZA), 2006)
This paper provides a new way of analyzing tenure profiles in wages, by modelling simultaneously the evolution of wages and the distribution of tenures. We develop a theoretical model based on efficient bargaining, where both log outside wage and log wage in the current job follow a random walk, as found empirically. This setting allows the application of real option theory. We derive the efficient separation rule. The model fits the observed distribution of job tenures well. Since we observe outside wages only at job start and job separation, our empirical analysis of within job wage growth is based on expected wage growth conditional on the outside wages at both dates. Our modelling allows testing of the efficient bargaining hypothesis. The model is estimated on the PSID.
Keywords: C51; C52; J63; 330; random prodictivity growth; efficient bargaining; job tenure; inverse gaussian; wage-tenure profiles; option theory; Betriebszugehörigkeit; Lohn; Erwerbsverlauf; Verhandlungstheorie; Realoption